2017
DOI: 10.1016/j.jceh.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatic and Extrahepatic Insults on the Outcome of Acute-on-Chronic Liver Failure

Abstract: Background: To study the differences in outcome and predictors of mortality in acute-on-chronic liver failure (ACLF) precipitated by hepatic or extrahepatic insults. Methods: Consecutive patients of cirrhosis with acute decompensation were prospectively included and followed up for 90 days from admission. ACLF was defined based on chronic liver failure (CLIF) acute-on-chronic liver failure in cirrhosis (CANONIC study) criteria. Acute worsening due to acute viral hepatitis A and E, hepatitis B flare, alcoholic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…The study showed the prevalence of AIH flare as a cause of ACLF in 2.8% of the ACLF patient cohort. This is in concordance with another study (20) in which AIH flare accounted for 2.5% of ACLF patients. DILI and acute viral hepatitis were found to precipitate flare of AIH in approximately 17% of patients.…”
Section: Discussionsupporting
confidence: 93%
“…The study showed the prevalence of AIH flare as a cause of ACLF in 2.8% of the ACLF patient cohort. This is in concordance with another study (20) in which AIH flare accounted for 2.5% of ACLF patients. DILI and acute viral hepatitis were found to precipitate flare of AIH in approximately 17% of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Singh et al recently reported that alcohol-related disease, not HBV, is the major cause of liver cirrhosis in Asia (11). We had also reported alcohol in 58-66% of patients, followed by NASH in 9-14% of patients, as a cause of cirrhosis (12)(13)(14). This is in accordance with Western data where NASH-related CLD is an upcoming epidemic and is becoming the leading cause of liver transplantation (15).…”
Section: Discussionsupporting
confidence: 89%
“…20 The main reason behind this proposal is the more severe prognostic value of HE in the context of ACLF, 21 even if there is no proof of peculiar pathophysiological mechanisms. 22 The finding that the increased brain water content is parallel with the degree of HE 23 is in line with the view of increased astrocyte hydration in HE. 24 It should be emphasized that the concept of brain hyperhydration ('edema') should not be confused with the one of intracranial hypertension.…”
Section: The Classification Of Hesupporting
confidence: 79%